Update of pathogen reduction technology for therapeutic plasma - Chakrabarty, P; Rudra, S; Hoque, MM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):308-11. The abstract of this article is available on the PubMed website